Voltage and frequency stability enhancement with an automatic voltage regulator and power system stabilizer in a ring-structured power system post generator loss - Zetty Adibah, Kamaruzzaman; Nur Zahirah, Mohd Ali; Ahmad Syahiman, Mohd Shah (Seventh Sense Research Group, 2025)
Generator loss resulting from failures and inadequate circuit breaker response time can lead to uncontrolled oscillations and possibly system instability. This issue becomes increasingly evident in systems that are small and interdependent among their components. Thus, it is critical to understand the system’s transient behavior during generator loss and the important control methods to mitigate the negative impacts. This study analyses the transient stability of the IEEE 9-bus test system in the context of generator loss and delayed circuit breaker response, emphasizing the impact of Automatic Voltage Regulator (AVR) and Power System Stabilizer (PSS) on damping reduction and transient recovery time. The simulation demonstrates that it is essential to clear the faults by opening the circuit breaker before the Critical Clearing Time (CCT) to maintain system stability. Incorporating AVR and optimizing PSS tuning contributes to less damping and accelerating transient recovery time. This allows the voltage dip and prolonged frequency oscillation to recover within the timeframes recommended by IEEE 1159 and IEEE 1547.